2019
DOI: 10.21082/littri.v25n2.2019.81-90
|View full text |Cite
|
Sign up to set email alerts
|

SIDIK LINTAS KARAKTER VEGETATIF DAN GENERATIF KELAPA DALAM DI DAERAH PASANG SURUT JAMBI / Path Coefficient Analysis of Vegetative and Generative Characters of Tall Coconut in Tidal Swamp Area of Jambi

Abstract: <p>Coconut improvement programs require knowledge of the effect of morphological characters on the coconut yield. The study aimed to determine the effects of fourteen morphological characters on the production of coconut meat character on Kampung Laut and Pengabuan tall coconut. This study was conducted in Kampung Laut and Pengabuan Villages, Jambi Province. Correlation analysis among 15 characters of vegetative, generative, and fruit components used the Walpole formula (1992). Fourteen characters affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, this criterion must have a close relationship with the yield so that if it is used as a selection criterion, it is effective. Miftahorrachman et al, 2019 identified that the characters of the weight of endosperm, the number of fruits, and the number of coconut bunches in Kampung Laut (Zabak), which had a close and positive relationship with the yielding character, namely coconut meat production, while 13 characters others analyzed did not have a direct relationship with the character of coconut meat production [7].…”
Section: The Variation Of Vegetative Charactersmentioning
confidence: 99%
“…However, this criterion must have a close relationship with the yield so that if it is used as a selection criterion, it is effective. Miftahorrachman et al, 2019 identified that the characters of the weight of endosperm, the number of fruits, and the number of coconut bunches in Kampung Laut (Zabak), which had a close and positive relationship with the yielding character, namely coconut meat production, while 13 characters others analyzed did not have a direct relationship with the character of coconut meat production [7].…”
Section: The Variation Of Vegetative Charactersmentioning
confidence: 99%